New Technologies for Sustainable Energy in the Smart City: the WET Theory - Fistola, Romano; La Rocca, Rosa Anna (TeMA - Journal of Land Use, Mobility and Environment, 2014)
<span id="docs-internal-guid-524da81f-bbba-6068-362c-42d8ae416cae" style="font-size: 15px; font-family: Calibri; color: #000000; background-color: transparent; font-weight: normal; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline;">The paper tries to develop a new approach to sustainable planning for the smart city. The relationship between new technologies and the urban system could be developed in a new way considering of the WET theory. The WET theory starts from the main components for establishment and the survival of the human settlements: Water, Energy and Technologies (WET). Considering this approach, the technology could be envisaged as a switch element for the biforcation that could be generated inside the process of management of the modern urban systems. From one end the technology can improve the use of renewable energies and promote a different way of use the energy inside the city. From the other end the technology can permit a huge structural works that can drive the urban system towards a worst dimension causing permanent change inside the territory as a whole particularly at large scale. The paper propose a focus on the two mentioned possibilities considering the best dimension, proposed by the DESERTEC project and the worst one prefigured by the South to North Water Diversion Project that is ready to start in China.